Isolated Tympanic Plate Fracture Frequency and Its Relationship to Mandibular Trauma. Issue 4 (November 2014) - Altay, Canan; Erdoğan, Nezahat; Batkı, Ozan; Eren, Erdem; Altay, Sedat; Karasu, Şebnem; Mete, Berna; Uluç, Engin
Purpose: This study evaluated the prevalence of isolated tympanic fractures and their correlation with mandibular fractures by using maxillofacial computed tomography (CT). Materials and Methods: We retrospectively evaluated the maxillofacial CT of 1590 patients who presented to our emergency department with maxillofacial trauma between December 2010 and December 2012. Maxillofacial CT was used as the criterion standard for evaluating patients with maxillofacial fractures. The CT images were evaluated by using an electronic picture archiving and communications system and interpreted independently by 2 radiologists. Results: The maxillofacial CT images revealed mandibular fractures in 167 of the patients and isolated tympanic plate fractures in 35 of these 167 patients. Four patients (11%) had a bilateral tympanic plate fracture, and 31 patients (89%) had unilateral tympanic plate fracture. Of all the tympanic plate fractures, 19 (54%) were on the right side and 16 (46%) were on the left side ( P > .05). In our results, a significant correlation between the presence of a right-sided tympanic plate fracture and fracture of the ipsilateral condylar process was found ( P = .036). However, a statistically significant difference between the presence of a tympanic plate fracture and other mandible fractures, additional soft-tissue findings, or the number of fractures was not determined ( P > .05). Sex had no impact on the presence of tympanic plate fracture ( P > .05). Conclusion: The frequency of isolated tympanic plate fractures in maxillofacial trauma is low, but it is an important anatomic location. Condyle fractures are significantly associated with isolated tympanic plate fractures. The presence of these injuries should raise suspicion of a concomitant isolated tympanic plate fracture.